EM BUSCA DA SINGULARIDADE PERDIDA: UMA JORNADA IMANENTE - Junior, Gerson Carlos Rigoni Bonfa (2020)
This is a theoretical research that seeks to think about what is a process of singularization or fulfillment of the plan of immanence in the language and subjectivity of man, as well as to think of ethical criteria that guarantee healthy follow-up to this